Carvacrol Essential Oil: A Natural Antibiotic against Zoonotic Multidrug-Resistant Staphylococcus Species Isolated from Diseased Livestock and Humans - Ahmed H. Abed (MDPI AG, 2021)
Staphylococcus species cause diseases in animals and humans. The prevalence and antimicrobial profiles of Staphylococcus spp. in animals and human samples in the Minya Governorate, Egypt, were determined, and resistance- and virulence-associated genes were observed in multidrug-resistant (MDR) isolates. Moreover, the antibacterial effect of carvacrol essential oil (EO) on the MDR isolates was studied. A total of 216 samples were aseptically collected from subclinically mastitic cow’s milk (n = 100), sheep abscesses (n = 25) and humans (n = 91). Out of 216 samples, a total of 154 single Staphylococcus species (71.3%) were isolated. The most frequent bacterial isolates were S. aureus (43%), followed by S. schleiferi (25%), S. intermedius (12%), S. xylosus (12%), S. haemolyticus (4.5%), S. epidermidis (2%) and S. aurecularis (1%). Haemolytic activity and biofilm production were detected in 77 and 47% of isolates, respectively. Antimicrobial susceptibility testing showed a high degree of resistance to the most commonly used antimicrobials in human and veterinary practices. The mecA, vanA, vanC1 and ermC resistance genes were detected in 93, 42, 83 and 13% of isolates, respectively. Moreover, hla, icaA and icaD virulence genes were detected in 50, 75 and 78% of isolates, respectively. Carvacrol effectively inhibited the growth of all tested isolates at concentrations of 0.1, 0.05 and 0.04% while a concentration of 0.03% inhibited 75% of isolates. Interestingly, some phenotypic changes were observed upon treatment with a carvacrol oil concentration of 0.03%. All the treated MDR Staphylococcus isolates changed from multidrug resistant to either susceptible or intermediately susceptible to 2–3 antimicrobials more than parental bacterial isolates. Real-time PCR was applied for the detection of the differential expression of mecA and vanC1 genes before and after treatment with carvacrol which revealed a mild reduction in both genes’ expression after treatment. Staphylococcus spp. Containing MDR genes are more likely to spread between humans and animals. From these results, carvacrol EO is a promising natural alternative to conventional antimicrobials for pathogens impacting human health and agriculture due to its potential antimicrobial effect on MDR pathogens; even in sub-lethal doses, carvacrol EO can affect their phenotypic properties and genes’ expression.